Analysis of BAP1 Germline Gene Mutation in Young Uveal Melanoma Patients. (June 2015) - Cebulla, Colleen M.; Binkley, Elaine M.; Pilarski, Robert; Massengill, James B.; Rai, Karan; Liebner, David A.; Marino, Meghan J.; Singh, Arun D.; Abdel-Rahman, Mohamed H.
Abstract Background: To evaluate the prevalence of BAP1 germline mutations in a series of young patients with uveal melanoma (UM), diagnosed before age 30. Materials and Methods: The study was carried out on 14 young uveal melanoma patients (average age 21.4 years, range 3 months to 29 years). Germline DNA was extracted from peripheral blood. BAP1 sequencing was carried out using direct sequencing of all exons and adjacent intronic sequences. We also tested for germline mutations in additional melanoma-associated candidate genes CDKN2A and CDK4 (exon 4). Results: We identified one patient with a pathogenic mutation (c. 1717delC, p.L573fs*3) in BAP1. This patient was diagnosed with UM at age 18 years and had a family history of a father with UM and a paternal grandfather with cancer of unknown origin. One additional patient had an intronic variant of uncertain significance (c.123-48T > G) in BAP1 while the remaining 12 patients had no alteration. None of the patients had CDKN2A or CDK4 (Exon 4) mutations. Family history was positive for a number of additional malignancies in this series, in particular for cutaneous melanoma, prostate, breast and colon cancers. There were no families with a history of mesothelioma or renal cell carcinoma. Conclusions: This study suggests that a small subset of patients with early onset UM has germline mutation in BAP1. While young patients with UM should be screened for germline BAP1 mutations, our results suggest that there is a need to identify other candidate genes which are responsible for UM in young patients.